Clinical and pharmacokinetics equivalence of multiple doses of levodopa benserazide generic formulation vs the originator (Madopar). Issue 11 (12th September 2019) - Torti, Margherita; Alessandroni, Jhessica; Bravi, Daniele; Casali, Miriam; Grassini, Paola; Fossati, Chiara; Ialongo, Cristiano; Onofrj, Marco; Radicati, Fabiana Giada; Vacca, Laura; Bonassi, Stefano; Stocchi, Fabrizio
Abstract : Aims: While several generic preparations of levodopa/carbidopa and levodopa/benserazide (LBD) are currently available, pharmacokinetic (PK) equivalence and therapeutic equivalence studies with levodopa generics are not available in Italy. Lack of data on generic formulations is a critical factor for their limited use in this country and often lead patients to refuse the generic version of the branded drug. Methods: An experimental, 2‐centre, randomized, double‐blind, 2‐sequence, noninferiority cross‐over study was designed to evaluate both the PK equivalence and clinical equivalence of multiple doses of the generic preparation of LDB, Teva Italia, compared to the originator (Madopar). Forty‐three out‐patients with a diagnosis of idiopathic Parkinson's disease on LDB, were recruited and randomly assigned to 1 of 2 study sequences: generic–originator or originator–generic. Clinical evaluations were performed at the end of each study period. A PK study with an LDB fixed dose (100 + 25 mg) was performed in a subpopulation of 14 subjects. Results: Clinical data showed a reduction of 0.49 and 1.54 in the mean UPDRS III scores for the LDB and the originator, respectively. The 95% CIs [−2.21: 0.11] of the mean difference original vs LDB are smaller than the clinically significant difference of 3 UPDRS III points, supporting the conclusion that the treatment with LDB is not inferior to the originator. No statistically significant differences were found with respect to area under the curve to last dose, half‐life, maximum concentration, time to maximum concentration and last observed concentration. Conclusion: These findings prove the therapeutic clinical equivalence as well the PK equivalence of the generic LDB and the originator (Madopar).